Effets De La Dynamique Du Couvert Végétal Sur Les Écoulements Dans Le Bassin Versant De La Lagune Aghien En Côte d‘Ivoire - Seydou, Diallo; Dabissi, Noufé; Armand, Tra Bi Zamblé; Amidou, Dao; Bamory, Kamagaté; Rose, Effebi Kôkôh; Lanciné, Goné Droh; Serge, Koffi Ehouman; Thierry, Koffi Jean; Paturel, Jean Emmanuel; et al. (European Scientific Journal, ESJ, 2018)
The aim of this paper is to highlight the impact of anthropization on the runoff Djibi and Bete rivers, tributaries of the Ivorian Aghien watershed. The classification method with the maximum likelihood used to the diachronic study of satellite imagery Landsat Thematic Mapper (1987), Enhance Thematic Mapper Plus (2000) and Operational Land Imager (2015) and Geographic Information System remote sensing has been applied. It has permitted to note the total disappearance of the forest at risk of subsistence crops, fallows, habitats and bare soils. The forest area that was 4 ha in 1987 for the Bete Watershed has been destroyed entirely. This change in the land cover between 1987 and 2015 had considerable consequencies on the contributions of water to the level of the Djibi and Bete rivers. So bad slight values of the retention capacity indices underneath 100 reflect the anthropization of these watersheds. The use of rainfall series for the evaluation on the runoff from the Vuilllaume Dubreuil method (1975), reveals an increase in runoff coefficients from 20% to 21% in Djibi watershed and from 13% to 17% in Bete watershed between 1987 and 2015. Increasing these flow coefficients related to water in a watershed more and more urbanized inflow is a threat to the water quality and the security of area urbanized.